A grounded theory approach to studying craft: The serious work and leisure of knitting. Issue 1 (1st March 2020) - Court, Kate
AbstractThe primary aim of this article is to exemplify and evaluate the application of a grounded theory approach to studying craft participants, including the introduction of social theory in the analysis process. This is done by describing a qualitative research project that explored why women today knit. An increased interest in knitting and other crafts has been noted, particularly amongst women participants. The article sets out how a grounded theory approach was employed to offer new ways to understand this topic. The secondary aim of this article is to share the findings of this research. It is suggested that what participants said about their relationship with knitting could be understood in terms of Stebbins' notions of creating routines for engaging in this leisure activity, fulfilling a sense of obligation to undertake the activity, and a sense of pride and autonomy. This helped frame knitting as an activity that requires hard work and perseverance but results in fulfilment. Furthermore, it was found that knitting deviates from Stebbins' conception of serious leisure activities as the categories of hobbyists, amateurs and professionals may need reworking, given that knitters (classed by Stebbins' as hobbyists without professional counterparts) are partly professionalized and therefore seem more appropriately classed as amateurs.